2014
DOI: 10.1002/elan.201400095
|View full text |Cite
|
Sign up to set email alerts
|

Application of Novel Zn‐Ferrite Modified Glassy Carbon Paste Electrode as a Sensor for Determination of Cd(II) in Waste Water

Abstract: This paper describes the preparation of a new sensor based on Zn‐ferrite modified glassy carbon paste electrode and its electrochemical application for the determination of trace Cd(II) ions in waste waters using differential pulse anodic stripping voltammetry (DPASV). Different Zn/Ni ferrite nanoparticles were synthesized and characterized using scanning electron microscopy (SEM) and X‐ray powder diffraction (XRPD). The prepared ferrite nanoparticles were used for the preparation of Zn‐ferrite‐modified glassy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Such behavior could be attributed to hydrogen adsorption onto surface of working electrode which was observed before [10,56]. Examination of accumulation time was investigated in the range 50–650 seconds at constant potential -1.4 V. As can be seen from the Fig 10B the current peaks for both Pb(II) and Cd(II) increase to 600 s and then become constant as is described previously [57]. Hence the optimal deposition conditions for simultaneous determination of Pb(II) and Cd(II) on GCE- MnCo 2 O 4 NPs were: accumulation potential of –1.4 V vs. Ag/AgCl, accumulation time of 600 s at pH 2 (H 2 SO 4 /HCl buffer).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Such behavior could be attributed to hydrogen adsorption onto surface of working electrode which was observed before [10,56]. Examination of accumulation time was investigated in the range 50–650 seconds at constant potential -1.4 V. As can be seen from the Fig 10B the current peaks for both Pb(II) and Cd(II) increase to 600 s and then become constant as is described previously [57]. Hence the optimal deposition conditions for simultaneous determination of Pb(II) and Cd(II) on GCE- MnCo 2 O 4 NPs were: accumulation potential of –1.4 V vs. Ag/AgCl, accumulation time of 600 s at pH 2 (H 2 SO 4 /HCl buffer).…”
Section: Resultssupporting
confidence: 66%
“…In Fig 11, it can be seen that there is a slight displacement of the peak potentials, in case of Cd(II) only. This displacement can be attributed to overlapping of diffusion layers resulting from the stripping of metal (M 0 ) from the surface of the electrode and the transition of metal ions (M 2+ ) into the solution [57]. Linear ranges of the proposed method were from 0.05 to 40 μmol/dm 3 for Pb(II) whereas oxidation current depends linearly on cadmium concentration in the ranges 0.05–1.6 and 1.6–40μmol/dm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Stankovic et al compared different types of ZnFe 2 O 4 and concluded that ZnFe 2 O 4 was the best option for the highest selectivity and responses of different HMIs. [74] They obtained the calibration plot for Cd(II), which was linear in the range of 0.01 to 0.5 µm with a detection limit of 0.38 ppb. Ns et al also investigated the performance of ZnFe 2 O 4 modified electrode for the measurements of Cd(II) and Pb(II) simultaneously.…”
Section: Zinc-based Electrodesmentioning
confidence: 99%
“…For example, the use of tellurium-based electrode was recently reported for the sensing of HMIs. [196] Finally, sustainability and eco-friendliness should be important factors to consider for the [74] ZnO nanofibers [73] Cd(II): 0.38 Pb(II): 0.397 Hg Hanging mercury drop electrode [83] Cd(II): 0.010 Pb(II): 0.010 Ga Hanging Galinstan drop electrode [51,100] Cd(II): 9.0 Pb(II): 2.0…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…The cations occupy two different positions in a spinel structure: tetrahedral (Zn) and octahedral (Fe) sites along the face-centered cubic lattice formed by O 2 - cations. The use of bimetallic oxides as electrode materials could enhance both electrical conductivity by two orders of magnitude and electrochemical activity versus materials prepared with unitary metal oxides [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%